PEMBELAJARAN IPA TERPADU MELALUI PROJECT BASED LEARNING DALAM MELATIHKAN ACADEMIC DAN SOCIAL SKILL SISWA SMP - Shofatun, Anis; Ibrahim, Muslimin; Wasis, Wasis (JPPS (Jurnal Penelitian Pendidikan Sains), 2016)
This research aims to describe practicality and effectiveness of the integrated science learning through project-based learning in fasilitate academic and social Skill of class VIIF SMP Muhammadiyah 12 GKB Gresik. This research uses one group prettest-posttest design proceded by preparatory phase which aims to develop the material planning of the 4-D models of Thiagarajan and followed by  implementation phase in the classroom. The results showed:1) the practicality of teaching material categorized in feasibility of lesson plan and students give positive responses toward teaching materials and implementation of project based learning, 2) the teaching and learning use the teaching material development categorized effectively in terms of : (a) an assessment of the student's academic skills in organizing materials, skills to plan, implement and report on project task and psychomotor student in the laboratory showed very good (b) assessment of social skills of students in collaboration and communication showed very good and (c) increased knowledge learning outcomes of students with an average of 0.8 N-gain (high gain). Based on the result, it can be concluded that project based learning in teaching integrated natural science for Junior High Students is practicable and effectively to fasilitate student’s academic and social skill and gaining their knowledge. Penelitian ini bertujuan mendeskripsikan kepraktisan dan keefektifan pembelajaran IPA terpadu melalui pembelajaran berbasis proyek dalam melatihkan keterampilan akademik dan sosial siswa kelas VIIF SMP Muhammadiyah 12 GKB Gresik. Penelitian ini menggunakan one group pretest -posttest  design yang di dahului dengan tahap persiapan yang bertujuan mengembangkan perangkat mengikuti rancangan 4-D model dari Thiagarajan dan dilanjutkan dengan tahap uji coba di kelas. Hasil penelitian ini menunjukkan: 1) perangkat pembelajaran berkategori praktis ditinjau dari keterlaksanaan rencana pembelajaran dan respon positif siswa terhadap pembelajaran berbasis proyek; 2) Pembelajaran menggunakan perangkat yang dikembangkan berkategori efektif, hal ini didasarkan pada: (a) penilaian keterampilan akademik siswa dalam mengorganisir materi, keterampilan merencanakan, melaksanakan dan melaporkan penugasan proyek, keterampilan unjuk kerja laboratorium menunjukkan sangat baik (b) penilaian keterampilan sosial siswa dalam bekerjasama dan berkomunikasi menunjukkan sangat baik (c) peningkatan hasil belajar pengetahuan siswa dengan rata-rata N-gain sebesar 0,8 (gain tinggi). Berdasarkan hasil penelitian di atas dapat disimpulkan bahwa pembelajaran berbasis proyek praktis dan efektif dalam melatihkan keterampilan akademik dan sosial siswa SMP serta meningkatkan hasil belajar pengetahuan pada mata pelajaran IPA Terpadu.